A cross-sectional study on prevalence of hypertension and pre-hypertension among young adults at urban field practice area, Gandhi Medical College, Secunderabad - Bolisetti, Venu; Yale, Padmavathi; M., Hima Bindu; Thomas, Vimala; ., Kavya; Kasam, Aishwarya (International Journal Of Community Medicine And Public Health, 2020)
Background: Hypertension is also known as high or raised blood pressure. It is a condition in which the blood vessels have persistently raised pressure. Hypertension is directly responsible for 57% of all stroke deaths and 24% of all coronary heart disease deaths in India. Young adults have been deemed to be at lower risk in their development of hypertension due to resultant gaps in the literature. Hence the present study was aimed to determine the prevalence of hypertension and pre-hypertension among young adults (18-35 years) residing in Urban Field Practice Area of Gandhi Medical College. Objectives of the study was to determine the prevalence of hypertension and pre-hypertension in young adults and to identify the risk factors and sociodemographic factors associated with hypertension and pre-hypertension. Methods: A sample of 233 young adults (18-35 years) was included in the community based cross sectional study by simple random sampling followed by systematic random sampling in Bholakpur. All the participants were assessed for blood pressure and BMI status. Data was analysed in MS Excel version 7.2 Software. Results: The prevalence of hypertension was 9.85% (n=23) and pre–hypertension was 23.65% (n=55). About 13.3% of the study population were smokers and 26.6% of them were alcoholics. Twenty seven percent of the study participants were obese and overweight. Conclusions: Higher proportion of hypertensives and pre-hypertensives were found in the category of males, smoking, alcohol intake and obesity than their counter ones.